2013
DOI: 10.1002/adv.21381
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Conformal Cooling Channels in Rapid Heat Cycle Molding: A Review

Abstract: Rapid heat cycle molding (RHCM) can eliminate the weld line, increase flow length, and improve surface quality of the molded parts. However, the cycle time is much longer as compared to the conventional injection-molding process due to the time taken to heat up and cool down the mold. This paper reviews the applications of conformal cooling channels to reduce the cycle time in rapid and hard tooling for the conventional injection-molding process. The performance of conformal cooling channels in reducing the cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(34 citation statements)
references
References 71 publications
(170 reference statements)
1
32
1
Order By: Relevance
“…ey attributed this high gloss surface to the amorphous phase, which completely wrapped all crystalline phases on the surface; finally, the surface presented a pure and uniform amorphous phase. However, this conclusion differs from the observations of other researchers [17,21,31] who indicated that the surface of the PP sample is composed of both crystalline and amorphous phases. Another researcher (Wang et al [35]) pointed out that, for the virgin PP, the surface gloss exhibited a different trend: instead of increasing, it tended to decrease as the cavity surface temperature continued to rise after reaching 110°C.…”
Section: Relationship Between Microstructure and Surface Glosscontrasting
confidence: 99%
See 1 more Smart Citation
“…ey attributed this high gloss surface to the amorphous phase, which completely wrapped all crystalline phases on the surface; finally, the surface presented a pure and uniform amorphous phase. However, this conclusion differs from the observations of other researchers [17,21,31] who indicated that the surface of the PP sample is composed of both crystalline and amorphous phases. Another researcher (Wang et al [35]) pointed out that, for the virgin PP, the surface gloss exhibited a different trend: instead of increasing, it tended to decrease as the cavity surface temperature continued to rise after reaching 110°C.…”
Section: Relationship Between Microstructure and Surface Glosscontrasting
confidence: 99%
“…e most evident difference between the RHCM and CIM processes is that the former employs dynamic mold temperature control technology whereby the mold temperature is rapidly increased to a preset temperature before the mold is filled with the melt. During the filling and packing stage, high temperature is maintained; thereafter, the melt is quickly cooled to demold it before proceeding to the next stage of the production cycle [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies [25][26][27][28][29][30][31] included applications such as induction heating with nanoscale molding, using low thermal inertia tools, weldlines at microscale, using infrared heating equipment, and in general on the improvement of microscale features/products. In common for all research is that a high mold temperature does improve the overall product quality and helps remedy the above-mentioned problems.…”
Section: Introductionmentioning
confidence: 99%
“…Shayfull et al [2] concluded that rapid heat cycle moulding, in which the mould is heated and cooled for each cycle is also likely to benefit greatly from conformal cooling, however this is yet to be fully explored. Au and Yu carried out computer aided engineering simulations to demonstrate the benefits of conformal cooling over conventional cooling for blow moulding tooling [3].…”
Section: Introductionmentioning
confidence: 99%